Beginning and duration of pregnancy in automated health care databases: review of estimation methods and validation results1. (28th January 2015) - Margulis, Andrea V.; Palmsten, Kristin; Andrade, Susan E.; Charlton, Rachel A.; Hardy, Janet R.; Cooper, William O.; Hernández‐Díaz, Sonia
Abstract: Purpose: To describe methods reported in the literature to estimate the beginning or duration of pregnancy in automated health care data, and to present results of validation exercises where available. Methods: Papers reporting methods for determining the beginning or duration of pregnancy were identified based on Pubmed searches, by consulting investigators with expertise in the field and by reviewing conference abstracts and reference lists of relevant papers. From each paper or abstract, we extracted information to characterize the study population, data sources, and estimation algorithm. We then grouped these studies into categories reflecting their general methodological approach. Results: Methods were classified into 5 categories: (i) methods that assign a uniform duration for all pregnancies, (ii) methods that assign pregnancy duration based on preterm‐delivery or health care related codes, or codes for other pregnancy outcomes, (iii) methods based on the timing of prenatal care, (iv) methods based on birth weight, and (v) methods that combine elements from 2 and 3. Validation studies evaluating these methods used varied approaches, with results generally reporting on the mistiming of the start of pregnancy, incorrect estimation of the duration of pregnancy, or misclassification of drug exposure during pregnancy or early pregnancy. Conclusions: In the absence of accurate information on the beginning or duration of pregnancy, several methods of varying complexity are available to estimate them. Validation studies have been performed for many of them and can serve as a guide for method selection for a particular study. Copyright © 2015 John Wiley & Sons, Ltd.